Holocene history of human impacts inferred from annually laminated sediments in Lake Szurpity, northeast Poland - Kinder, Malgorzata; Tylmann, Wojciech; Bubak, Iwona; Filoc, Magdalena; Gasiorowski, Michal; Kupryjanowicz, Miroslawa; Mayr, Christoph; Sauer, Laurentius; Völlering, Ulrich; Zolitschka, Bernd (Journal of Paleolimnology, 2019)
Annually laminated lake sediments provide high-resolution and accurate timescales for reliable paleoenvironmental reconstructions. We investigated human activity in a low-human-impact region of Poland, taking advantage of varved sediments from Lake Szurpily, which span the last 8200 years. Multiple sediment variables indicated that catchment evolution and lacustrine responses, mainly to changes in forest cover, were divided into four phases. Because of sparse or only seasonal occupation of settlements in NE Poland, human impact in the region was insignificant until ca. 939 +/- 55 BC (lacustrine phase I). During Phase II (939 +/- 55 BC-AD 1392 +/- 38), we recorded an increase in human indicators, reflecting the direct influence of a Yatvingian community. Afterwards, between AD 1392 +/- 38 and 1770 +/- 30 (phase III), permanent settlements and agricultural land use stabilized. The beginning of the last period (phase IV) was clearly identified by all sediment variables, which responded simultaneously to local human activities. Disappearance of laminae from AD 1858 +/- 22 until about AD 1997 indicated disturbance of pre-existing, stable depositional conditions, followed by environmental recovery in the last 20 years. Such recovery may have been related to recent socio-economic changes and establishment of a park that reduced human influence on the lake.
CRIS-Team WoS Importer:2019-04-23